Enhancing Numeric Literacy of Students at SMAN 1 Gunungsari Lombok, Indonesia through Pascal Programming - Taufik, Muhammad; Hikmawati, Hikmawati; Susilawati, Susilawati; Arduha, Jannatin; NNSP, Verawat (Jurnal Pengabdian Masyarakat Sains Indonesia (Indonesian Journal Of Science Community Services), 2023)
The purpose of this training activity is to enhance the numerical literacy of students at SMA Negeri 1 Gunungsari, Lombok, Indonesia within the context of physics education. Pascal programming is introduced as a tool to assess students' progress in understanding numerical literacy. The training results indicate a significant improvement in students' numerical literacy, with an average numerical literacy score of 7.68 before the training and 8.94 after the training. These findings reflect the positive contribution of integrating Pascal programming into physics education toward enhancing numerical literacy.